Summer reading ebook - McKinlay, Jenn (2023)
When a woman who’d rather do anything than read meets a swoon-worthy bookworm, sparks fly, making for one hot-summer fling in New York Times bestselling author Jenn McKinlay's new rom-com. For Samantha Gale, a summer on Martha’s Vineyard at her family’s tiny cottage was supposed to be about resurrecting her career as a chef, until she’s tasked with chaperoning her half-brother, Tyler. The teenage brainiac is spending his summer at the local library in a robotics competition, and there’s no place Sam, who has dyslexia, likes less than the library. And because the universe hates her, the library’s interim director turns out to be the hot-reader guy whose book she accidentally destroyed on the ferry ride to the island. Bennett Reynolds is on a quest to find his father, whose identity he’s never known. He’s taken the temporary job on the island to research the summer his mother spent there when she got pregnant with him. Ben tells himself he isn't interested in a relationship right now. Yet as soon as Sam knocks his book into the ocean, he can’t stop thinking about her. An irresistible attraction blossoms when Ben inspires Sam to create the cookbook she’s always dreamed about and she jumps all in on helping him find his father, and soon they realize their summer fling may heat up into a happily ever after.